Kūrybingumas žinių visuomenėje: idėjų žemėlapis - Glosienė, Audronė (Information & Media, 2007)
Pomodernioje žinių (žinojimo) visuomenėje vykstančios permainos siejamos su intelektinio, socialinio, kultūrinio ir kitų „minkštojo“ kapitalo formų efektyvaus naudojimo paieškomis. XXI a. pradžioje vėl imta plačiai kalbėti apie kūrybingumą kaip ne tik nesenkantį organizacijų, valstybių ir miestų atsinaujinimo šaltinį, bet ir kaip svarbiausią naujojo amžiaus dimensiją apskritai. Šio požiūrio plėtrai didžiausios įtakos turėjo JAV tyrėjo Richardo Floridos darbai, jie ir apžvelgiami šiame straipsnyje kartu su naujausiais kultūrinės geografijos ir kultūrinės ekonomikos tyrimais, atskleidžiančiais fizinės vietos svarbą kūrybingumo sklaidai.Creativity in the Knowledge Society: a map of ideasAudronė GlosienėSummarKnowledge society puts more emphasis on intellectual, social, cultural and other forms of “soft” capital than on the “hard” forms of it. Big hopes and expectations for growth and development are connected with the effective use of knowledge in all spheres of human life. But many authors today emphasize that it is not the production of knowledge but its transfigurations and diffusions that make a difference and that not scientific knowledge itself but creativity is the main resource of the postmodern knowledge society.Traditionally, creativity is connected to cultural field and is perceived as a prerequisite for artistic activities. Today, the notion of creativity has expanded to cover different types of technical, intellectual, entrepreneurial and other creativity. Furthermore, it is very often defined and understood broadly, as underlying quality of almost all activities. Postmodern society does not value obedient performance of predefined tasks; it wants innovation in every step and moment. Creativity is one of the basic concepts that unites both arts and culture, science, research, and contemporary business where execution of prescribed tasks is no longer seen as valuable asset. Innovation, ability to see things “from a different angle” becomes one of the most desired features of human capital in any firm or organization. Such “obsession” with creativity was much influenced by Richard Florida whose views and postulates are explored in this article alongside with the concepts of new economical and cultural geography on the paradox of place and space in the virtual world.The more today’s life and work is wired, the more freedom people have to choose when and from where to work. Traditional offices are no longer needed, cities and areas created during the industry age (houses, schools, shops, kindergartens built around the plant there the father works) are no longer attractive for young people who find these infrastructures obsolete and not inspiring as they lead completely different life-style the former generation did. They look both for a challenging work also inspiring and dynamic surroundings for living and going out. Cultural regions, innovation regions, cities of culture and knowledge cities, innovation corridors, “third places” – all these geographically-based concepts and phenomena show the importance of geographical proximity in the world that has declared it’s virtuality. Huge amount of new geographical and urban research shows how important is the physical space in the virtual age.